A paradigm shift in African agricultural research for development: the role of innovation platforms. Issue 2 (2nd April 2016) - Sanyang, Sidi; Taonda, Sibiri Jean-Baptiste; Kuiseu, Julienne; Coulibaly, N'Tji; Konaté, Laban
Abstract : To demonstrate the development impact of their outputs, agricultural research and development (R&D) organizations used to focus on the efficiency and effectiveness of technologies. In recent years, innovation systems thinking has started to address institutional and organizational barriers to technological change in African agriculture. The main approach used has been the multi-stakeholder innovation platform (IP). This paper analyses the requirements for improving the competence and skills of IPs actors in agricultural value chains, food systems, and natural resource management. As case studies, it uses IPs in the maize and cassava value chains that were initiated in the dissemination of new agricultural technologies in Africa (DONATA), in both West and Central Africa, and made reference to the rice IPs facilitated by AfricaRice. Yields and incomes in maize and cassava IPs significantly increased and inter-actor relationships and behavioural change among the diverse social and economic operators were enhanced. This achievement built on three capacity development interventions: (i) learning workshops that sensitized and informed technocrats and policy-makers and nurtured their involvement and ownership, (ii) competence and skill training of IP facilitators and practitioners, and (iii) coaching and mentoring of these facilitators and practitioners. To better facilitate IPs, facilitators and practitioners need to learn to observe, recreate, test, and perfect the IP process and value chain approach. Practicable tools that can be visualized and put into practice by the IP actors are essential. The DONATA on which the paper is based has been invaluable in terms of experiential learning.